Tumor Venéreo Transmissível Canino: relato de caso - Maciel, Luis Felipe de Araujo (Universidade Federal do Tocantins, 2024)
The supervised internship report aims to clarify the activities carried out throughout the period, in addition to acquiring professional experience in the veterinarian's area of activity, and can be complemented and/or compared with information found in the literature. The internship took place at the Veterinary Clinical Pathology Laboratory (LPCV) of the University Veterinary Clinic of the Federal University of Northern Tocantins (CVU - UFNT), Araguaína-TO, under the supervision of veterinarian Helena Pena Rodrigues Ferreira and guidance from Profª. Dr. Andressa Francisca Silva Nogueira, from August 14th to October 25th, 2023, totaling 400 hours. During the internship period, 1005 exams were carried out, including internal and external care, with biochemical analyses, followed by blood count and total plasma protein being the most frequent. Of the biochemical analyzes performed, creatinine was the most requested, followed by urea, alanine aminotransferase and alkaline phosphatase. One of the activities carried out included the case report of a dog with suspected Transmissible Venereal Tumor, summarized in this report.